(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Abstract: Surgical treatment is a feasible option for pelvic organ prolapse. Vaginal hysterectomy and pelvic floor repair is the operation of choice. For prevention of recurrence of prolapse fixation of vaginal vault to sacrospinous ligament is done . This is known as sacrocolpopexy. In this study sacrospinous colpopexy is performed as an adjunctive procedure at the time of vaginal hysterectomy to prevent recurrence of prolapse. Materials and Methods: This prospective observational study was conducted in the Department of Gynaecology and Obstetrics of Bangabandhu Memorial Hospital, USTC from 1.1.19 to 31.12 19 for a period of one year. The purpose of this study was to evaluate the feasibility of this procedure along with vaginal hysterectomy and to assess the outcome in terms of complications , need of removal of fixation suture and recurrence of prolapse. Result: Out of 72 pelvic organ prolapse patients, 24(38.7%) were in the age group between 51-60 years and 53(85.4%) were postmenopausal, 46(77.7%) came from rural community, 42(67.8%) delivered more than 5 children. Among them 70(99.9%) cases vaginal delivery were responsible factors, and 96.6% (60) had Stage III prolapse by POP-Q staging . During performing fixation of vaginal vault with sacrospinous ligament in 10(13.8%) cases there were difficulty in access of pararectal space, and in 13(18.1%) cases felt difficulty during placement of the suture. Severe back pain were felt in 25(33.4%) cases ,20(32.4%) cases had retention of urine after removal of catheter, and 20(32.4%) cases felt buttock pain in postoperative period. One patient required removal of suture due to pain and discomfort within the vagina .All patients came 72(100%) for follow up after 6weeks. POP-Q examination was done during follow up. Wound infection was not detected in any cases. Patients satisfaction regarding symptoms were good. Conclusion: Sacrospinous colpopexy is an effective procedure during pelvic organ prolapse surgery as it restores vaginal supports, maintain good vaginal length and depth. So at the time of vaginal hysterectomy sacrospinous colpopexy may be adjunctive procedure to prevent recurrence and relieve of symptoms . Bangladesh J Obstet Gynaecol, 2021; Vol. 36(2): 114-119